2007
DOI: 10.1007/s11325-007-0132-z
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity in relation to age as predictor of severity of sleep apnea in children with snoring

Abstract: Correlation between obesity and obstructive sleep apnea has been documented in both adults and children. This investigation evaluated importance of body mass index (BMI) in relation to age as predictor of severity of obstructive sleep-disordered breathing (SDB). Children with habitual snoring referred for polysomnography were recruited. BMI Z score (> or =1.036 vs <1.036, i.e. at risk for overweight or overweight vs normal) was assessed as predictor of severity of SDB (apnea-hypopnea index [AHI] >five vs < or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
1
7

Year Published

2007
2007
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 31 publications
3
37
1
7
Order By: Relevance
“…Some studies reported an association between HS and male sex [7,11,15], being overweight [12,17,18], parental smoking [6,13,14], breastfeeding [18] and low socioeconomic status [5,7,19], while others did not confirm these findings. Some of these discrepancies might be due to age differences between study populations [20]. An excess of respiratory symptoms related to atopic diseases has been previously reported [6,7,12,17,18,21].…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Some studies reported an association between HS and male sex [7,11,15], being overweight [12,17,18], parental smoking [6,13,14], breastfeeding [18] and low socioeconomic status [5,7,19], while others did not confirm these findings. Some of these discrepancies might be due to age differences between study populations [20]. An excess of respiratory symptoms related to atopic diseases has been previously reported [6,7,12,17,18,21].…”
mentioning
confidence: 87%
“…This is unlikely to be due to lack of statistical power. However, there are data suggesting that the association between obesity and snoring might change with age [20] and that BMI might play a minor role in the aetiology of snoring in preschool children, in contrast to adolescence and adulthood [12,17,18]. In young children, with relatively noncollapsible upper airways, obesity per se might not elicit the noise of snoring.…”
Section: Association With Clinical Featuresmentioning
confidence: 99%
“…13 The exclusion of OSA 13 is particularly relevant, considering that obesity markedly increases the risk for sleep-disordered breathing. [14][15][16] OSA is a highly prevalent condition in children, in which intermittent occlusion of the upper airway during sleep leads to recurrent oxyhemoglobin desaturations, elevated CO 2 levels, sleep fragmentation, and reduced sleep effi ciency. Similar to obesity, OSA is associated with multifaceted derangements in metabolic and cardiovascular function, including endothelial dysfunction.…”
Section: Sphygmomanometrymentioning
confidence: 99%
“…Examples of such conditions include congenital or acquired craniofacial anomalies with fixed anatomical narrowing of the upper airway, the presence of neuromuscular dysfunction, prematurity, Down syndrome (41), achondroplasia (42), cerebral palsy, and myelomeningocele (43). In addition, and of particular importance, is the presence of obesity as a major and significant risk factor for OSA in children (44)(45)(46)(47)(48)(49).…”
Section: Pathophysiology Of Osa In Childhoodmentioning
confidence: 99%